2023
DOI: 10.1161/jaha.122.027646
|View full text |Cite
|
Sign up to set email alerts
|

Omega‐3 Fatty Acids and Heart Rhythm, Rate, and Variability in Atrial Fibrillation

Abstract: Background Previous randomized control trials showed mixed results concerning the effect of omega‐3 fatty acids (n‐3 FAs) on atrial fibrillation (AF). The associations of n‐3 FA blood levels with heart rhythm in patients with established AF are unknown. The goal of this study was to assess the associations of total and individual n‐3 FA blood levels with AF type (paroxysmal versus nonparoxysmal), heart rate (HR), and HR variability in patients with AF. Methods and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…We considered that the serum EPA level was associated with the degree of parasympathetic nervous tone because previous studies have reported that a high n‐3 PUFA level increases the parasympathetic nervous tone 37 and decreases the heart rate. 38 In fact, we confirmed a lower heart rate during sinus rhythm after ablation among the high EPA/AA, EPA alone, EPA + DHA, and EPA/DHA groups. Regarding the higher risk of EPA on AF recurrence, a study reported that AF could be induced by simultaneous sympathetic and parasympathetic nervous stimulation.…”
Section: Discussionsupporting
confidence: 66%
“…We considered that the serum EPA level was associated with the degree of parasympathetic nervous tone because previous studies have reported that a high n‐3 PUFA level increases the parasympathetic nervous tone 37 and decreases the heart rate. 38 In fact, we confirmed a lower heart rate during sinus rhythm after ablation among the high EPA/AA, EPA alone, EPA + DHA, and EPA/DHA groups. Regarding the higher risk of EPA on AF recurrence, a study reported that AF could be induced by simultaneous sympathetic and parasympathetic nervous stimulation.…”
Section: Discussionsupporting
confidence: 66%
“…The latter finding is in line with a previous analysis of the Swiss AF study, showing no significant association of total n -3 FAs with the type of AF. In patients with known AF, neither total nor individual fish- or plant-derived n -3 FAs showed a significant correlation with an increased AF burden, i.e., non-paroxysmal AF [ 36 ]. Whether n -3 FA supplementation in low or high dosages affects the burden of AF in patients with known AF remains to be determined in future randomized controlled trials.…”
Section: Discussionmentioning
confidence: 99%
“…DHA and total n-3 PUFA level, but not EPA level, was associated with a slower heart rate. 127 Several observational studies have shown that increased serum and red blood cell membrane levels of EPA, but not DHA, are associated with AF. 116,128 A recent multinational pooled meta-analysis of 54 799 community-dwelling individuals free from CVD or at relatively low risk, from 17 prospective cohort studies, with a median follow-up of 13.3 years, including 7720 cases of incident AF, found that levels of docosapentaenoic acid, DHA, and EPA+DHA, but not EPA alone, were associated with lower incidence of AF (HR, 0.89 [95% CI, 0.83-0.95]; HR, 0.90 [95% CI, 0.85-0.96]; and HR, 0.93 [95% CI, 0.87-0.99], respectively).…”
Section: N-3 Pufa and Af: Epidemiologic Studiesmentioning
confidence: 99%